2022
DOI: 10.2147/ijn.s328090
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubble Ozone Stored in Hyaluronic Acid Decorated Liposomes: Antibacterial, Anti-SARS-CoV-2 Effect and Biocompatibility Tests

Abstract: Purpose SARS-CoV-2-infected individuals may be asymptomatic, and therefore, the virus is highly contagious. We aimed to develop an agent to control viral replication in the upper respiratory tract and to prevent progression of the disease into the lower airways as well as inter-individual transmission. For this purpose, we investigated the antibacterial and antiviral activities of our novel nanobubble ozonated hyaluronic acid-decorated liposomal (NOHAL) solution, developed by using nanotechnology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Due to the water-retaining properties of hyaluronic acid, its healing effects, and ability to moisturize the mucosa, nanobubble ozone is stored in hyaluronic acid-decorated liposomes. 11 Our ozone solution (1,600 ppm) is produced as a nasal spray, and all biocompatibility and toxicity tests (skin, oral, nasal, eye) of the product have been performed. 11 Zerillo et al 26 reported that ozonated liposomal products inhibited bacterial viability and eradicated P. aeruginosa and S. aureus biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the water-retaining properties of hyaluronic acid, its healing effects, and ability to moisturize the mucosa, nanobubble ozone is stored in hyaluronic acid-decorated liposomes. 11 Our ozone solution (1,600 ppm) is produced as a nasal spray, and all biocompatibility and toxicity tests (skin, oral, nasal, eye) of the product have been performed. 11 Zerillo et al 26 reported that ozonated liposomal products inhibited bacterial viability and eradicated P. aeruginosa and S. aureus biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our ozone solution (1,600 ppm) is produced as a nasal spray, and all biocompatibility and toxicity tests (skin, oral, nasal, eye) of the product have been performed. 11 Zerillo et al 26 reported that ozonated liposomal products inhibited bacterial viability and eradicated P. aeruginosa and S. aureus biofilms. Silva et al 10 described how ozonated oils had a moderate to high ability to eliminate adhered cells and a high capacity to eradicate 24 hours old biofilms produced by MRSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 As a major component of the cellular matrix, HA is derived from glycosaminoglycan in animal connective tissues. 24 As a bio-material, HA exhibits many inherent functions, for example, water-retaining, 25 antibacterial, 26 scavenging free radical, 27 and bio-compatibility, 28 respectively. Due to these merits, HA is widely used as a food additive in fruit juice, 29 soya-bean milk, and jelly, respectively.…”
Section: Introductionmentioning
confidence: 99%